1989
DOI: 10.3354/meps050263
|View full text |Cite
|
Sign up to set email alerts
|

Significance of advection for the carrying capacities of fjord populations

Abstract: Advective rates of nutrients, phytoplankton and zooplankton were estimated for the Masfjord, western Norway, in June and October 1985. The advective contribution to the phytoplankton biomass formation was dearly less than the local growth. Advection of nutrients, even below the photic zone, may have large implications for the new production of the fjord. The highest renewal rate (13.6 % d l ) due to advection was obtained for the mesozooplankton in June. While 20 % of this renewal was due to water advection al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 8 publications
3
69
0
Order By: Relevance
“…Nevertheless, models have shown that predatory control can occur even at moderate consumption rates (Davis 1984). However, in an advective system, planktonic predators are not a part of the usual predator-prey relationship as described by the LotkaVolterra equations (Aksnes et al 1989). No significant correlation between volumes of B. infundibulum and mesozooplankton biomass ( p > 0.05) was found.…”
Section: Seasonal Variations Of Ctenophoresmentioning
confidence: 80%
“…Nevertheless, models have shown that predatory control can occur even at moderate consumption rates (Davis 1984). However, in an advective system, planktonic predators are not a part of the usual predator-prey relationship as described by the LotkaVolterra equations (Aksnes et al 1989). No significant correlation between volumes of B. infundibulum and mesozooplankton biomass ( p > 0.05) was found.…”
Section: Seasonal Variations Of Ctenophoresmentioning
confidence: 80%
“…Seasonal variation in circulation patterns and transport of nutrients and biota are important factors determining the carrying capacities of fjord populations. Previous studies have indicated that residual currents and vertical distribution of Calanus finmarchicus and euphausiids determine the direction of their transport at a nearly steady state (Aksnes et al 1989). Considering diel vertical migration of zooplankton, seasonal residual and tidal currents, the transport of zooplankton by currents is not in a steady state in northern Norwegian fjords.…”
Section: Introductionmentioning
confidence: 92%
“…Common phenomena are advection of zooplankton by coastal currents or jets, and entrapment of zooplankton in convergent eddies. In fjords and estuaries, advection by tidal and residual currents leads to more complicated tidal period distribution and transport of zooplankton (Lindahl & Hernroth 1988, Aksnes et al 1989, Gupta et al 1994. Freshwater runoff can lead to a net surface flux outward and a bottom intrusion nonlinearly coupled with periodic tidal currents (Kaartvedt & Svendsen 1995, Zhou 1998a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These habitats feature varyingly brackish water, higher summer temperatures than the open ocean and refuge from advective losses. While the upper layers of fjords are characterized by estuarine circulation transporting brackish water out of the fjord and, below it, coastal water into the fjord, water exchange below sill level is much reduced, facilitating the retention of plankton and formation of resident populations (Aksnes et al, 1989;Sørnes et al, 2007;Hosia & Bamstedt, 2008). This kind of overwintering strategy is used by the lobate ctenophore Bolinopsis infundibulum in Malangen fjord, northern Norway (Falkenhaug, 1996).…”
Section: Source -Sink Dynamicsmentioning
confidence: 99%